Analisis Dampak Keberadaan Ritel Modern terhadap Keuntungan, Pendapatan, dan Jumlah Pembeli Usaha Ritel Tradisional di Kecamatan Banjarmasin Utara - Ade Nur Fatimah, Gusti; Rizali, Rizali (PPJP ULM, 2025)
This study aims to determine whether there are differences in profits, income and the number of traditional retail buyers before and after the existence of modern retail in North Banjarmasin District. In this study using a quantitative descriptive research type using primary data obtained from a questionnaire. The analysis technique used in this study is to use the paired sample t-test where the calculation of this technique is to find out whether there are differences in profits, income and the number of traditional retail buyers before and after the existence of modern retail.